Modelling of Swarm Communication - Jaafar, Anuar; Hamidon, Abdul Hamid; Anas, Abd Latiff; Hazli Rafis, Abdul Rahim; Mohd Yusof, Haziezol Helmi; Mohd Saad, Wira Hidayat (2013)
Swarm communication is a communication process of sending data within a certain area via agents.. Data will be sent to all the agents in this process. This is also closely related to the way of broadcasting via “short communication” as a way to find out the data among their agents. This field involved an in -depth study of the behaviour of the agents and by using a homogeneous approach, inspect the process of sending data. This includes investigation of independence of agents and the characteristics of sending and receiving data for a random process in a swarm. In this paper, techniques useful for swarm implemented bit-communication behaviour will be presented. There are two approaches that are used to send and receive signals. The reverse approach is where data can be resend to the sender for the next cycle, where the program randomly selects the nearest agents t o send data to. While for the nonreversing approach data is not able to return to the sender in the previous cycle. The non -reversing approach can improve system performance and efficiency. This paper presents the development of a swarm communication mode l and how it can be used to illustrate the communication process.